Pengaruh Profitabilitas Pada Kebijakan Dividen Dengan Likuiditas dan Kepemilikan Manajerial Sebagai Variabel Pemoderasi - Devi, A.A.Ayu Mirah Varthina; Suardikha, I Made Sadha; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
Dividend policy became an important financial policies, not only in terms of management of the company, but also of shareholders. The shareholders will propose a dividend if the company managed to record a profit. The purpose of this study is to determine the effect of profitability on dividend policy and whether the liquidity and managerial ownership can moderate the effect of profitability on dividend policy. Sampling technique in this study using purposive sampling and sample 104 observations obtained after deducting the data outliers. And MRA multiple regression was used to analyze the data in this study. The results showed that the higher the profitability, the higher the dividend payout ratio (dividend policy), while liquidity and managerial ownership is not a variable moderating effect of profitability on dividend policy. Keywords : Profitability, Liquidity, Managerial Ownership, Dividend Policy
Keywords: Profitability, Liquidity, Managerial Ownership, Dividend Policy